HOW DISTRIBUTIONAL CONFLICTS THEORY EXPLAIN FACTORS AFFECTING INSTITUTIONAL CHANGES IN CORAL REEF GOVERNANCE? LESSONS LEARNED FROM GILI INDAH VILLAGE, WEST LOMBOK INDONESIA - Aceng Hidayat (JOURNAL OF COASTAL DEVELOPMENT, 2007)
This article aims at explaining factors affecting the successfulness of coastal communities of Gili Indah in constructing a governance structure of coral reef management. Coral reef management in this region has changed from an ineffective state regime to a local governance. From the perspective institutional economic theories, the emergence of a governance is an institutional change phenomena that are affected, among others, by actors’ characteristics such as organizational experiences, opportunistic behavior, environmental awareness/perception, planning horizon, bargaining power, technological skill and certainty; and trust, distrust and reputation. Using a distributional conflict theory of institutional change, the results of this research can draw a conclusion that institutional change process of coral reef management in the locality was strongly assumed affected by those factors.